Fuzzy AHP recommender system for selecting computer component / Muhammad Zarfan Fakhri Mohmed Yasir - Mohmed Yasir, Muhammad Zarfan Fakhri (2022)
Computers have always been the topic in technological advancements in these days. Starting from a device for addition and subtraction of simple numbers, to solving math problems, and to simulating a virtual space for various purposes. In order to keep up with the evolving technology, computer parts have been improving in terms of performance since desktop computers were invented. Because of this improvements, many technology companies have introduced different products for different purposes. However, the numerous different parts have been confusing for people with little knowledge of computer parts. This project’s objective is to develop a mobile application for selecting the proper computer parts for desktop computer, enabling user to customize the desktop computer according to the need of the user and to evaluate the usability of the system. For this project, Fuzzy AHP technique is used to compare the parts according to the user’s need criteria to recommend the computer parts. Flutter extension in Android Studio is used to develop the mobile application. The application was developed as prototype and it will be able to recommend some lists of complete computer parts. The interface will be simple as it will suit the purpose of this project, which is to simplify the process of selecting computer components.